Small cell bladder cancer: should we consider prophylactic cranial irradiation? - Morgan, Tara Nikonow (Int Braz J Urol, 2019)
PURPOSE: To describe the clinical characteristics, treatment patterns, and outcomes in patients with small cell bladder cancer at our institution, including those who received prophylactic cranial irradiation (PCI) for the prevention of intracranial recurrence. MATERIALS AND METHODS: Patients with small cell bladder cancer treated at a single institution between January 1990 and August 2015 were identified and analyzed retrospectively for demographics, tumor stage, treatment, and overall survival. RESULTS: Of 44 patients diagnosed with small cell bladder cancer, 11 (25%) had metastatic disease at the time of presentation. Treatment included systemic chemotherapy (70%), radical surgery (59%), and local radiation (39%). Six patients (14%) received PCI. Median overall survival was 10 months (IQR 4 – 41). Patients with extensive disease had worse overall survival than those with organ confined disease (8 months vs. 36 months, respectively, p = 0.04). Among those who received PCI, 33% achieved 5 - year survival. CONCLUSION: Outcomes for patients with small cell bladder cancer remain poor. Further research is indicated to determine if PCI increases overall survival in small call bladder cancer patients, especially those with extensive disease who respond to chemotherapy.